Diseño e implementación de un prototipo automatizado de silla de ruedas con propulsión eléctrica basada en tecnología de bajo coste. - Cabrera Ordóñez, Xiomara Anahí (2023)
Research work and technological advances have been evolving, allowing greater comfort for human beings; one of these advances is the trend of automation of traditional processes. This research project details the design and implementation of a prototype of a low-cost electric wheelchair capable of controlling movements to facilitate the independent and comfortable movement of people with physical disabilities, improving their autonomy and their relationships and raising their quality of life, in addition to contributing to the fulfillment of four of the seventeen Sustainable Development Goals. At a general level, we implemented this work in five phases, including information gathering, design, acquisition, implementation, and evaluation; therefore, we oriented the subcomponents of the prototype toward the deployment of the basic needs for its operation. For this reason, in the first instance, we conducted the corresponding research work based on the physical deficiencies affecting people at the level of their lower limbs and their respective assistive technologies, focusing specifically on both manual and electric wheelchairs. Subsequently, we established the operating parameters of the wheelchair, which allowed us to select and size an electric propulsion system consisting of two brushless motors and a lithium-ion battery. We based the control and automation system on the programming of an Arduino controller board that works as the brain of the process and a joystick that allows the movements of the prototype facilitated by employing a program based on the operation requirements and other characteristics for its correct control and management. In the same way, for the assembly of all the power and control components, we designed and built a structure to allow easy assembly and maintenance in addition to providing flexibility, comfort, and safety to the user. Finally, once we implemented the different systems of the prototype, we proceeded to the validation of the design and operation specifications through field tests; in the same way, we made a financial analysis to know the costs involved in the implementation of the prototype and to verify the cost reduction concerning existing models in the market. Keywords: control systems, electric motors, physical disabilities, wheel chair.